A nanoliter fluidic platform for large-scale single nucleotide polymorphism genotyping - Douglas G. Roberts; Tom B. Morrison; Shau Neen Liu-Cordero; Jamie Cho; Javier Garcia; Tanya S. Kanigan; Kevin Munnelly; Colin J.H. Brenan (BioTechniques)
Discovery, evaluation, and understanding the biological relevance of single nucleotide polymorphisms (SNPs) and their associated phenotypes is relevant to many applications, including human disease diagnostics, pathogen detection, and identification of genetic traits impacting agricultural practices, both in terms of food quality and production efficiency. Validation of putative SNP associations in large-scale cohorts is currently impeded by the technical challenges and high cost inherent in analyzing large numbers of samples using available SNP genotyping platforms. We describe in this report the implementation of the 5′-exonuclease, biallelic PCR assay for SNP genotyping (TaqMan) in a nanofluidic version of a high-density microplate. System performance was assessed using a panel of 32 TaqMan SNP genotyping assays targeted to human polymorphisms. This functional test of the nanoliter fluidic SNP genotyping platform delivered genotyping call rates and accuracies comparable to the same larger volume reactions in microplate systems.